Novel mutations in ZP1: Expanding the mutational spectrum associated with empty follicle syndrome in infertile women. Issue 4 (18th January 2021) - Wu, Ling; Li, Menghui; Yin, Mingru; Ou, Yangjie; Yan, Zhiguang; Kuang, Yanping; Yan, Zheng; Li, Bin
Abstract: Empty follicle syndrome (EFS) is a serious and complex reproductive complication for infertile women suffering from the recurrent failure of oocyte retrieval in an in vitro fertilization procedure, and its pathogenesis remains obscure. Increasing evidence highlights the genetic basis of EFS occurrence. In this study, we identified two novel missense mutations (c.1127G > A, p.C376Y and c.325C > T, p.R109C), two novel frameshift mutations (c.800_801delAG, p.E267Gfs*80 and c.1815_1825delGGTCCTTTTGC, p.V606Afs*42), one novel nonsense mutation (c.199G > T, p.E67Ter), and three reported mutations (c.769C > T, p.Q257Ter; c.1430 + 1G > T, p.C478Ter and c.1169_1176delTTTTCCCA, p.I390Tfs*16) in five unrelated probands, showing similar EFS manifestations, which expands the mutational spectrum of individuals with autosomal recessive ZP1 . Current research will provide a better understanding of the biological functions of ZP1, and some insight into the determination of ZP1 variation as an additional rule for assessing the EFS disease. Abstract : Novel mutations in ZP1: expanding the mutational spectrum associated with empty follicle syndrome in infertile women.